ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) BERDASARKAN IKLIM ORGANISASIONAL DAN KETERIKATAN KERJA MELALUI MOTIVASI KERJA PADA PERAWAT RUMAH SAKIT UMUM DAERAH INDRASARI RENGAT - Syamsuri, Abd. Rasyid; Meliantika, Mely; Novrianti, Dian Puspita (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2024)
This research aims to analyze the influence of organizational climate and length of service on Organizational Citizenship Behavior through work motivation in nurses at Indrasari Rengat Regional Hospital. The population in this study were all nurses at Indrasari Rengat Regional Hospital, totaling 153 people. In this study, the sample size is also included in the total sample because this study uses total sampling or a saturated sampling technique. This research uses primary data obtained from distributing questionnaires distributed to all nurses at Indrasari Rengat Regional Hospital as an instrument to prove research results and test hypotheses using path analysis. The data analysis method uses SPSS (Statistical Product Service Solution) and Smart Partial Square Software (SmartPLS). The results of this research show: 1) organizational climate has a positive and significant effect on OCB, 2) length of service has a positive and significant effect on OCB, 3) organizational climate has a positive and significant effect on work motivation, 4) work years has a positive and significant effect on work motivation , 5) work motivation has a positive and significant effect on OCB, 6) organizational climate has a positive and significant effect on OCB through work motiva